Fundamentals of medical-surgical nursing : a systems approach - Brady, Anne-Marie, 1965-; McCabe, Catherine; McCann, Margaret (Chichester, West Sussex, UK : John Wiley & Sons, 2013)
"Fundamentals of Medical Surgical Nursing is a comprehensive yet accessible textbook on medical and surgical nursing designed to inform and guide learning related to the nursing care of the adult patient. It provides a foundation in anatomy and physiology, pathophysiology, medical management, and nursing care for the spectrum of adult health conditions. Divided into two sections, the first looks at common principles underlying medical and surgical nursing practice. In section two, students will be able to apply relevant anatomy and physiology to enhance their understanding and inform their nursing care of medical and surgical conditions"--Provided by publisher.
Machine generated contents note: Preface -- List of contributors -- Part 1: Common principles underlying medical and surgical nursing practice -- 1. Principles of nursing assessment / Naomi Elliott -- 2. Principles of drug administration / Sue Jordan -- 3. Principles of intravenous therapy / Lisa Dougherty -- 4. Principles of nutritional care / Carolyn Best and Helen Hitchings -- 5. Principles of infection prevention and control / Sile Creedon and Maura Smiddy -- 6. Principles of acute care for older people / Louise Daly, Debbie Tolson and Anna Ayton -- 7. Principles of end of life care / Kevin Connaire -- 8. Principles of peri-operative nursing / Joy O'Neill, Bernie Pennington and Adele Nightingale -- 9. Principles of high dependency nursing / Tina Day -- 10. Principles of emergency nursing / Valerie Small, Gabrielle Dunne and Catherine McCabe -- Part 2: Adult medical and surgical nursing -- 11. Nursing care of conditions related to the skin / Zeena Moore and Julie Jordan O'Brien -- 12. Nursing care of conditions related to the respiratory system / Anne Marie Corroon and Geralyn Hynes -- 13. Nursing care of conditions related to the circulatory system / Kate Olson and Tracey Bowden -- 14. Nursing care of conditions related to the digestive system / Joanne Cleary-Holdforth and Therese Leufer -- 15. Nursing care of conditions related to the urinary system / Margaret McCann, Ciara White and Louisa Fleure -- 16. Nursing care of conditions related to the endocrine system / David Chaney and Anna Clarke -- 17. Nursing care of conditions related to the neurological system / Elaine Pierce and Mary E. Braine -- 18. Nursing care of conditions related to the immune system / Michael Coughlan and Mary Nevin -- 19. Nursing care of conditions related to haematological disorders / Mairead Ni Chonghaile and Laura O'Regan -- 20. Nursing care of conditions related to the musculoskeletal system / Sonya Clarke and Julia Kneale -- 21. Nursing care of conditions related to the ear, nose, throat and eye / Dympna Tuohy, Jane McCarthy, Carmel O'Sullivan and Niamh Hurley -- 22. Nursing care of conditions related to reproductive system / Debra Holloway and Louisa Fleure. Index.
Includes bibliographical references and index.
Keywords: Perioperative Nursing